The growth delusion wealth, poverty, and the well-being of nations - Pilling, David (New York Tim Duggan Books, 2018)
A provocative critique of the pieties and fallacies of our obsession with economic growth We live in a society in which a priesthood of economists, wielding impenetrable mathematical formulas, set the framework for public debate. Ultimately, it is the perceived health of the economy which determines how much we can spend on our schools, highways, and defense; economists decide how much unemployment is acceptable and whether it is right to print money or bail out profligate banks. The backlash we are currently witnessing suggests that people are turning against the experts and their faulty understanding of our lives. Despite decades of steady economic growth, many citizens feel more pessimistic than ever, and are voting for candidates who voice undisguised contempt for the technocratic elite. For too long, economics has relied on a language which fails to resonate with people's lived experience, and we are now living with the consequences. In this powerful, incisive book, David Pilling reveals the hidden biases of economic orthodoxy and explores the alternatives to GDP, from measures of wealth, equality, and sustainability to measures of subjective wellbeing. Authoritative, provocative, and eye-opening,The Growth Delusionoffers witty and unexpected insights into how our society can respond to the needs of real people instead of pursuing growth at any cost"
Includes bibliographical references (pages 259-280) and index.
Keywords: Economic development